Meningkatkan Motivasi Belajar Siswa Kelas V SD Muhammadiyah Integratif Dukun Pada Proses Pembelajaran Pendidikan Kewarganegaraan dengan Metode Pembelajaran Kooperatif Tipe Jigsaw - Devita Indah Puspitasari; Farid Syahrul Azhar; Intan Aminatul Khasanah; Kun Hisnan Hajron (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the learning motivation of the SDMuhammadiyah Integrative Shaman in grade 4. This study used a collaborative classroomaction research method, where the researcher acted as the executor of the action and theteacher acted to observe the process of the action. This classroom action research aims toincrease the learning motivation of fifth grade students of SD Muhammadiyah IntegratifDukun. That in cycle 1 out of 10 fifth grade students in cycle 1 only 4 students or 40% meetthe KKM and overall from 4 students the average score obtained of 76.25. In cycle 2generally categorized as GOOD (in descriptive scale) as many as 1 student or 8.0% StronglyAgree, then there are 9 students or 92.00% who are categorized Agree. The increase instudent learning motivation based on this is optimal because students who get scores belowthe Minimum Completeness Criteria (KKM) of 72 are no longer available and studentswho are above KKM 100% mean that Cycle 2 learning is successful or COMPLETE.